2013
DOI: 10.14221/ajte.2013v38n6.3
|View full text |Cite
|
Sign up to set email alerts
|

Intentions and Behaviours: Record-Keeping Practices of Pre-Service Teachers During Professional Experience

Abstract: The current expectation of teachers in Australia is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
(6 reference statements)
1
1
0
Order By: Relevance
“…ERMA New Zealand participants explained that their workload influenced their ability to perform the recordkeeping responsibilities expected of them; if they were busy, then managing records became a lower priority task. This is similar to the finding by S.G. Shaw et al (2013) that inconvenience and prioritisation of tasks limited the use of the EDRMS. Some ERMA New Zealand participants felt that completing recordkeeping related tasks was a requirement in addition to their primary role and something to do when they were not busy:…”
Section: Organisational Characteristicssupporting
confidence: 88%
See 1 more Smart Citation
“…ERMA New Zealand participants explained that their workload influenced their ability to perform the recordkeeping responsibilities expected of them; if they were busy, then managing records became a lower priority task. This is similar to the finding by S.G. Shaw et al (2013) that inconvenience and prioritisation of tasks limited the use of the EDRMS. Some ERMA New Zealand participants felt that completing recordkeeping related tasks was a requirement in addition to their primary role and something to do when they were not busy:…”
Section: Organisational Characteristicssupporting
confidence: 88%
“…This suggestion that ICTs make it burdensome for staff to save records was also explored by S. G Shaw, Pedersen, Cooley and Callingham (2013) who investigated how pre-service teachers used an EDRMS to collect, record, interpret and use classroom data on their students during professional experience. The research identified a range of themes that prevented or limited the ability of the participants to use the EDRMS in ways that aligned with their intentions, including:…”
Section: Understanding the Recordkeeping Behaviours Of Individualsmentioning
confidence: 99%